UPAYA PENYELESAIAN SENGKETA TANAH DI AREA KAWASAN HUTAN LINDUNG REGISTER 45 MILIKNEGARA OLEH PEMDA DI KABUPATEN MESUJI PROVINSI LAMPUNG - Intan pelangi Andika setiawan Ridhwan (Muhammadiyah Law Review Journal, 2022)
This study is to find out the efforts made by the Regional Government in overcoming Land Disputes in the Protected Forest area of Register 45 in the Mesuji Regency, Lampung Province. in the Mesuji Regency, Lampung Province and what are the obstacles in this effort.This study uses a type of empirical juridical research, which is an approach that refers to written regulations or other secondary legal materials. The study was conducted in Mesuji Regency, Lampung Province where land conflicts occurred, the data collection techniques used were observation, interviews, documentation.Efforts to resolve land conflicts that have been taken by the local government of Mesuji Regency are related to the Register 45 Area between PT. Silva Inhutani Lampung with the community has carried out regional control and implemented the Partnership Program. Suggestions: That the government should immediately make efforts in handling agrarian conflicts thoroughly so that it does not spread to other social conflicts, the Police immediately act decisively and immediately arrest thugs/huggers who interfere with partnership and security in register 45, In the long term the central government and local governments seek to relocate residents register by relocating these residents to other areas so that the forest area becomes an appropriate area, considering the economic needs of the community who depend on the land they currently occupy.